CHANGES IN VERTICAL TRADE PATTERNS IN HIGH-TECHNOLOGY COMPANIES IN EAST JAVA - Wenny Restikasari; Dyah Wulan Sari; Angga Erlando; Fery Dwi Riyanto (East Java Economic Journal, 2019)
This study aims to insvestigate the impact of vertical trade pattern as export intensity, vertical trade integration and two-way trade dummy to firm production capability. This study deals with firm level data of East Java high-tech manufacturing induesties, employs as generalized method of moments (GMM) approach to examine the most imprortant factor of a vertical trade phenomenom. In the full-sample, the result demonstrates that vertical trade integration and two-way trade are significant determinants on firm’s production while export intensity is not. In ordinary trader sub-sample, export intensity is a significant determinant of firm’s production, whereas in vertical trader sub-sample export intensity is not.